La habitualidad en la enajenación de inmuebles y el impuesto a la renta - Hernández Berenguel, Luis (2013)
In the case of a natural person, conjugal community or an undivided succession domiciled in Peru which generates capital gains by transferring immovable goods, the profit generated is taxed with income tax andmay be graded as second category income –capital gain– or third category income–entrepreneurial income. From the analysis of Peruvian legislation, the author explains how the regularity in the transfer of immovable goods is configured to grade the profit made as second category income –when, over a year´s time, no more than two goods are transferred– and how, from the third transfer onward, the income will qualify as a third category income. Likewise, the author puts in evidence how the transfer of immovable goods occupied as a home is not considered as a capital gain when the seller does not generate third category income.